Cognitively Engaging Physical Activity for Targeting Motor, Cognitive, Social, and Emotional Skills in the Preschool Classroom: The Move for Thought preK-K Program - Vazou, Spyridoula; Mavilidi, Myrto F. (Frontiers in Psychology, 2021)
Despite the growing body of research indicating that integrated physical activity with learning benefits children both physically and cognitively, preschool curricula with integrated physical activities are scarce. The “Move for Thought (M4T) preK-K” program provides activities on fundamental motor skills that are integrated with academic concepts, executive function, and social-emotional skills in the preschool environment. The aim of this study was to evaluate the feasibility, usability, and effectiveness of the M4T preK-K program over an eight-week period in 16 preschool centers (N = 273; Mage =4.22 SD = 0.61) that were randomly assigned to the intervention (8 M4T; n = 138; Mage =4.31 SD = 0.61) and the control (8 traditional; n = 135; Mage =4.13 SD = 0.60) groups. In both groups, teacher ratings of children’s attention, behavioral control, and social skills (i.e., cooperation, assertion, and self-control) in the classroom, as well as children’s perceived motor skill competence and executive functions, were collected before and after the intervention. A daily teacher log measured intervention fidelity and perceived experiences with the program. Results showed a significant improvement on attention scores for children in the M4T preK-K group, compared to the control group. No significant differences emerged for behavioral control, social skills, executive functions, and perceived motor competence among groups. A significant time effect was evident for executive functions, with both groups improving over time. Further, the program was well-received, easy to implement in the preschool classroom and with high rates of satisfaction for both children and teachers. The M4T preK-K program is promising in helping teachers prepare preschool children for future educational success.